Spring - Herriges, Ann (Minneapolis, MN : Bellwether Media, 2007)
"Simple text and supportive images introduce beginning readers to the characteristics of the season of spring. Intended for students in kindergarten through third grade"--Provided by publisher
Includes bibliographical references (p. 23) and index
2.2
Keywords: Spring -- Juvenile literature; Readers (Elementary); Spring